The perceptions of students towards ESL classroom interactions in collaborative learning / Nur Hafizah Zuraini - Zuraini, Nur Hafizah (Faculty of Education, 2014)
Collaborative learning is a popular method used in teaching English as a second language. Even though collaborative learning has been applied in the teaching English among university students, the impact of its instruction varies according to the classroom interaction and the students who respond to it. Therefore, the study attempts to investigate the perceptions of students towards ESL classroom interaction in collaborative learning among students of tertiary level. A total of thirty 8th semester students of UiTM's TESL program were selected as the respondents of the study. This study was a survey research with only one group design. The data was collected through questionnaire with fifteen Likert-scale items and six open ended questions. The findings have shown that students of TESL in UiTM, Shah Alam, have positive perception towards classroom interaction in collaborative learning. On the other hand, the findings also showed that the ESL students also face challenges in collaborative based activities. From the findings of this study, useful recommendations are suggested to provide further references for future researches to be conducted in this field.